Restoring trust in corporate Malaysia - Ahmad Sharif, Nurretina; Ahmad Sharif, Zakie (Universiti Utara Malaysia, 2004)
Following the financial crisis in 1997 that created economic and social turmoil, good corporate governance has become the new watchwords. This paper highlights the importance of corporate governance to restore faith in its system. It traces briefly the background and its development in Malaysia. The paper also examines the outstanding legal and non-legal issues and challenges and suggests some recommendations to restore faith in its current system.